2021
DOI: 10.21037/gs-20-782
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram for prediction of lymph node metastasis in early-stage breast cancer

Abstract: Background: Lymph node status is an important factor in determining the prognosis of early-stage breast cancer. We endeavored to build and validate a simple nomogram to predict lymph node metastasis (LNM) in patients with early-stage breast cancer.Methods: Patients with T1-2 and non-metastasis (M0) breast cancer registered in the Surveillance, Epidemiology, and End Results (SEER) database were enrolled. All patients were divided into primary cohort and validation cohort in a 2:1 ratio. In order to assess risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Therefore, the prognostic value of the Ki67 index in breast cancer needs to be further explored. The cutoff value for age (41 and 55 years) was consistent with the age range of perimenopausal and menopausal Chinese women, although it was different from those of other studies [ 8 , 13 , 15 , 23 , 27 ]. Hence, our models showed high consistency to the currently available gold standard, such as the PR factor.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Therefore, the prognostic value of the Ki67 index in breast cancer needs to be further explored. The cutoff value for age (41 and 55 years) was consistent with the age range of perimenopausal and menopausal Chinese women, although it was different from those of other studies [ 8 , 13 , 15 , 23 , 27 ]. Hence, our models showed high consistency to the currently available gold standard, such as the PR factor.…”
Section: Discussionsupporting
confidence: 44%
“…The test is performed in approximately 20 to 100% of patients with breast cancer at different hospitals in China; the instances where 100% of breast cancer patients were tested were mainly clinical trials. Furthermore, recently, the prognostic value of the classic clinicopathologic variables is being reconsidered [ 3 8 ]. Some evidence indicates that clinicopathologic variable models are excellent surrogates for prognostic gene signatures [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nomogram identified 8 clinicopathological variables that were associated with SLN positivity: age, tumor size, tumor type, tumor location, lymphovascular invasion, multifocality, estrogen receptor status and progesterone receptor status [ 21 ]. Other studies supported the MSKCC nomogram findings that age, tumor size, histopathology, estrogen receptor status and progesterone receptor status were valuable predictors of SLN status [ 22 , 23 ]. A study from Thailand demonstrated that the MSKCC nomogram could accurately predict the probability of SLN metastasis for Thai breast cancer patients, however, only tumor size, histopathology, location, lymphovascular invasion, multifocality and progesterone receptor status were found to be significantly associated with SLNs metastasis [ 24 ].…”
Section: Discussionmentioning
confidence: 76%
“…Multiple recent studies have presented prediction models for noninvasive staging of axillary nodal (N) status with the long-term aim of replacing SLNB for subgroups of patients with breast cancer [5][6][7][8][9][10][11][12][13][14][15][16][17]. Only routinely and preoperatively available data should be used for a feasible noninvasive diagnosis of axillary N status aimed at clinical implementation.…”
Section: Introductionmentioning
confidence: 99%